Long‐lasting neurotoxic effects of exposure to methylmercury during development. (22nd April 2013) - Ceccatelli, S.; Bose, R.; Edoff, K.; Onishchenko, N.; Spulber, S.
Abstract Amongst environmental chemical contaminants, methylmercury (MeHg) remains a major concern because of its detrimental effects on developing organisms, which appear to be particularly susceptible to its toxicity. Here, we investigated the effects of low MeHg levels on the development of the nervous system using both in vitro and in vivo experimental models. In neural stem cells (NSCs), MeHg decreased proliferation and neuronal differentiation and induced cellular senescence associated with impairment in mitochondrial function and a concomitant decrease in global DNA methylation. Interestingly, the effects were heritable and could be observed in daughter NSCs never directly exposed to MeHg. By chronically exposing pregnant/lactating mice to MeHg, we found persistent behavioural changes in the male offspring, which exhibited depression‐like behaviour that could be reversed by chronic treatment with the antidepressant fluoxetine. The behavioural alterations were associated with a decreased number of proliferating cells and lower expression of brain‐derived neurotrophic factor (Bdnf) mRNA in the hippocampal dentate gyrus. MeHg exposure also induced long‐lasting DNA hypermethylation, increased histone H3‐K27 tri‐methylation and decreased H3 acetylation at the Bdnf promoter IV, indicating that epigenetic mechanisms play a critical role in mediating the long‐lasting effects of perinatal exposure to MeHg. Fluoxetine treatment restored the Bdnf mRNA expression levels, as well as the number of proliferating cells in the granule cell layer of the dentate gyrus, which further supports the hypothesis that links depression to impaired neurogenesis. Altogether, our findings have shown that low concentrations of MeHg induce long‐lasting effects in NSCs that can potentially predispose individuals to depression, which we have reported earlier to occur in experimental animals exposed to MeHg during prenatal and early postnatal development.